On the artistic heritage of Ivan Petrovich Larionov, The autor of «Kalinka»and our fellow townsman - Korzh, L.M. (Perm Federal Research Centre Journal, 2019)
It was found out 30 years ago that our best-loved song «Kalinka», earlier thought to be a folk tune, has a real author. This discovery was followed by the search of the composer’s artistic heritage that hadn’t been completed yet. However, nowadays we are quite aware of the author’s personality, his musical and social activity and the projection of Larionov’s gifted nature in his descendants.In 2020 we are going to celebrate two significant dates: the 190th anniversary of the composer’s birth and the 160th anniversary of the song that became the symbol of Russia. Some musical and thematic sessions will be timed to coincide with the dates at the PFRC UB RAS music hall. They will take place in a proven format of «Gribushin’s assemblies» successfully combining an informative part (a report, an announcement or a presentation) and the concert. The article describes the study of the composer’s artistic heritage in chronological order, publications and exclusive concert performances in the historical mansion of PFRC UB RAS.